James W. Barker, John’s Use of Matthew (Emerging Scholars; Fortress: Minneapolis 2015) - Adamczewski, Bartosz (The Biblical Annals, 2018)
Book review: James W. Barker, John’s Use of Matthew (Emerging Scholars; Fortress: Minneapolis 2015). Pp. XIX + 150. $59,00. ISBN 978-1-4514-9027-5 DOI: https://doi.org/10.31743/ba.2018.8.3.06